PROPOSED KEY PERFORMANCE INDICATOR DEVELOPMENT FOR ENGLISH PRESTASI LEARNING CENTER USING A HYBRID APPROACH - Herdiwan, Aysha
Measuring performance has become obligatory for every company in order to improve their current performance. Doing some tasks without knowing the current performance will result in less effective outcome that is probably not close to what company desired. Therefore, the development of Key Performance Indicators (KPI) will be needed as the performance standard to assess whether the jobs are performed well or not. English Prestasi Learning Center (EPLC), one of developing English courses in Bandung, is highly aware of that and has also initiated to move towards KPI development to improve its performance and even to outperform its competitors. That EPLC has not incorporated KPI in its performance management is an issue to be addressed for an immediate solution. Hence, this paper is intended to help solve the issue currently faced by the company by proposing a set of Key Performance Indicators that is developed through a comprehensive method and analysis. In order to make sure that the proposed KPIs are relevant enough to indicate the company’s success, they are set out from the vision and mission of the company’s that have been translated into a strategy portrayed in a strategy map using the perspective of Balanced Scorecard. The Balanced Scorecard will help the determination of KPI to comprise all substantial perspectives for company’s success such as financial, customer, internal business process, and learning and growth perspective. Most of the data required to develop the KPI is obtained through a qualitative method by conducting some interviews and observation. As for the finalized KPI, a quantitative method is utilized to determine the priority of each indicators by calculating the weight with Analytical Hierarchy Process. The result of this research show that EPLC, an organization which runs in an education sector, specifies its priority around learning and growth perspective (36.8%) in order to generate an excellent human capital, and so an ethical point of view is also utilized as a supporting indicator which forms a hybrid approach-a combination of balanced scorecard perspective and ethical climate. The finalized design of the KPI results in 21 indicators from 4 perspectives and will be included into the performance appraisal system. To be more practical, those KPIs are cascaded to divisional level so that each division can focus on improving the indicators with which they are assigned.